2007
DOI: 10.1007/s12011-007-0061-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Nutritional Status in Adolescents with Down Syndrome

Abstract: Studies have evidenced that zinc metabolism is altered in presence of Down syndrome, and zinc seems to have a relationship with the metabolic alterations usually present in this syndrome. In this work, the Zn-related nutritional status of adolescents with Down syndrome was evaluated by means of biochemical parameters and diet. A case-control study was performed in a group of adolescents with Down syndrome (n=30) and a control group (n=32), of both sexes, aged 10 to 19 years. Diet evaluation was accomplished by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
(26 reference statements)
1
11
0
1
Order By: Relevance
“…Mean values of 12.8 and 8.4 μg/mL were found for erythrocyte Zn in groups D and C, respectively. Purice et al [28] and Marques et al [29] also observed higher erythrocyte Zn concentration in children and in adolescents with DS when compared with those in the control group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Mean values of 12.8 and 8.4 μg/mL were found for erythrocyte Zn in groups D and C, respectively. Purice et al [28] and Marques et al [29] also observed higher erythrocyte Zn concentration in children and in adolescents with DS when compared with those in the control group.…”
Section: Discussionmentioning
confidence: 90%
“…Data showing a fall in zinc concentration in plasma may reflect a redistribution of the mineral by the organism, not necessarily an inhibition of its absorption [29]. Increased Zn concentration in erythrocytes and decrease in plasma may occur due to the presence of carbonic anhydrase, since Zn participates in its structure [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Soto-Quintana et al [23] and Marques et al [24], zinc concentration in plasma was evaluated in children with DS, and hypozincemia was identified with a significant difference regarding the control group. Yenigun et al [25] also observed low zinc levels in plasma of DS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have evidenced that Zn metabolism is altered in children with Down syndrome and Zn levels appear to be related to the metabolic alterations typical of this syndrome. In particular, adolescent patients with Down syndrome presented altered Zn levels for some cellular compartments and the average Zn concentrations were low in plasma and urine and elevated in erythrocytes [24]. Also, learning impairment, dyslexia, and autism may be associated to variations in trace elements concentration [25][26][27][28].…”
Section: Reference Values In Specific Groups Of Population: the Childmentioning
confidence: 99%